2014
DOI: 10.1016/j.egypro.2014.07.156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Rubber Contents on Biodegradation and Water Absorption of Interpenetrating Polymer Network (IPN) Hydrogel from Natural Rubber and Cassava Starch

Abstract: Interpenetrating polymer network (IPN) hydrogel based on crosslinked natural rubber (NR) latex and crosslink cassava starch (St) was successfully prepared by a solution blending technique. Crosslinked NR latex was firstly prepared in emulsion state at 70°C by using potassium persulfate as initiator and N, N'-methylene-bis-acrylamide (MBA) as crosslinker. Secondly, the crosslinked NR latex was mixed then with gelatinized cassava starch and maleic acid (MA) as crosslinker for starch at ambient temperature by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…As LNR was incorporated into the PLA, the moisture absorption increased to 0.85% as compared to that of PLA. The hydrophilicity was imparted by the LNR component which possessed higher hydrophilicity after modification from natural rubber through unsaturated double bonds, although raw natural rubber is a well‐known hydrophobic polymer . Meanwhile, the addition of PANI did not show significant changes in the moisture absorption compared to PLA/LNR.…”
Section: Resultsmentioning
confidence: 99%
“…As LNR was incorporated into the PLA, the moisture absorption increased to 0.85% as compared to that of PLA. The hydrophilicity was imparted by the LNR component which possessed higher hydrophilicity after modification from natural rubber through unsaturated double bonds, although raw natural rubber is a well‐known hydrophobic polymer . Meanwhile, the addition of PANI did not show significant changes in the moisture absorption compared to PLA/LNR.…”
Section: Resultsmentioning
confidence: 99%
“…The rubber samples were then immersed in toluene at room temperature for one week. The crosslink density was calculated using the Flory–Rehner equation: pc=prefix−12Vsnormalln()1Vr0+Vr0+χVr02Vr01true/3()Vr0true/2 where p c is the crosslink density (mol m −3 ), V s is the molar volume of toluene (1.069 × 10 −4 m 3 mol −1 ) at 25 °C, χ is the interaction parameter (0.44 + 0.18 V r 0 ) and V r 0 is the fraction of rubber in the swollen gel, which can be calculated as follows: Vr0=11+()ρrtrue/ρs[]()WSWDtrue/WD where ρ s and ρ r are the densities of toluene (0.87 g mL −1 ) and rubber (0.92 g mL −1 ), respectively, and W S and W D are the weights of swollen and dried rubbers, respectively…”
Section: Methodsmentioning
confidence: 99%
“…MD simulation, which is integrated with an iterative solution of Newton's equation of motion, is one of the most fundamental methods available for studying physical properties, typically like diffusivities and their corresponding residence times, through analyzing adequately penetrating trajectories of the atoms of a substance . In the past decades, much research based on MD simulation has been reported on the behavior and mechanism of small molecules: typically like O 2 , CO 2 , and N 2 to diffuse into polymers, metals, or minerals . In addition, MD simulation can allow observing the real‐time process of water absorption and analyzing water absorption behavior of polyoxymethylene under different hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%